Reactive Thrombocytosis – Aetiology And Relationship with Different Hematological Parameters, ESR, CRP in Infections - Garg, Bhavana; Shah, Menka (Annals of Pathology and Laboratory Medicine, 2020)
Background: The measurements of platelet count, mean platelet volume (MPV), WBC are routinely available nowadays. The aim of this study was to determine aetiology and relationship of these parameters whether they were associated with the known markers of disease activity, erythrocyte sedimentation rate (ESR) and C- reactive protein (CRP) in infections. Methods: This descriptive study was done on 500 patients with platelet count > 450,000/ μl and the cause being reactive. Platelet count, WBC, MPV, ESR, and CRP were measured at the time of hospitalization. Result: Most common cause of reactive thrombocytosis was Infections (28.8%), Tissue damage (16.4%), Iron deficiency anemia (16.2%), Malignancy (9.6%) and Inflammation (9.4%). In infections, bacterial infections (88%) were found to be more common. There was low degree of positive correlation between reactive thrombocytosis and WBC (r = 0.124, P >0.05) , ESR ( r = .147, P= 0.07) , MPV ( r = .077, P >0.05) in infections. There was significant negative correlation between reactive thrombocytosis and CRP in infections (r = -.199, P= 0.017). Conclusion: This study demonstrated a higher level of platelet count and lower MPV in all the patients having reactive thrombocytosis irrespective of it’s etiology. There was low degree of positive correlation between platelet count and WBC, ESR and MPV in infections and a significant negative correlation with CRP. We propose that platelet parameters may be considered as reliable markers for assessment of disease activity.